Deteksi Dini Perilaku Agresif Akibat Game Online pada Remaja - Alisya I’tiqafah; Mardhotillah Mardhotillah; Risma Anita Puriani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The rapid development of digital technology and its increasing number of users have led to increased use of online games among adolescents. A frequently encountered behavioral problem is aggressive behavior resulting from online gaming. The research method used was a literature review by examining various previous research articles relevant to the research topic. The sources used were scientific journals discussing aggressive behavior due to online gaming in adolescents. The collected data were then analyzed descriptively to obtain an overview of the level of tendency for aggressive behavior to emerge, which is influenced by the intensity of online gaming. The results of the study showed a significant relationship between aggressive behavior and the intensity of online gaming. Therefore, the implication is that guidance and counseling should not only focus on behavioral management but also efforts to detect early and prevent it through assessment, early screening of risky behavior, information services, psychoeducation on digital literacy, play time management, and emotional management. Collaboration between guidance counselors, teachers, and parents is crucial in integrating students' behavioral development sustainably, so that guidance and counseling services become a system that plays a role in reducing the risk of aggressive behavior due to online gaming in adolescents.